Pengaruh Waktu Adsorpsi Minyak Jelantah Sebagai Bahan Pembuatan Biodiesel Dengan Tanah Liat Terhadap Kualitas Biodiesel - Ahmadi, Ahmadi; Suyanti, Ika; Tikrahsari, Sri Astuti; Aini, Miftahul (Hydrogen: Jurnal Kependidikan Kimia, 2018)
Population growth and industrial development cause oil fuel consumptionincreases, so availability will thinning because it cannot be renewed. So toovercome that the government issued Presidential Decree No.10 of 2006concerning Development of Vegetable Fuels. Biodiesel is one of themrenewable alternative energy sources which are processed from vegetable oilswith use alcohol and NaOH as catalysts through the transesterificationprocess. Used cooking oil is one source of vegetable oil that can used as rawmaterial for making biodiesel through the process transesterification. But theuse of used cooking oil directly without through the adsorption process willaffect the quality of the biodiesel produced. The purpose of this study is todetermine the effect of adsorption time used cooking oil for the quality ofbiodiesel produced from used cooking oil. This research aimed to know thereis or no effect of odsorption time of cooking oil using the clay towardsbiodiesel quality. Object of this research used cooking oil which is adsorptedwith varieties time of adsorption was 0 hour (Control), 12 hours, 36 hoursand 48 hours. Based on the result of research showed that adsorption timehas effect towards quality, where high adsorption time was 12 hours. Qualityof biodiesel has been suitable with SNI. The quality was dencity 0,860 gr/cm3,water degree 0,035% vol, flame coordinate 170oC and acid number 0,71 mgKOH/g oil % the result of biodiesel 55,29%.